Critical Discourse Analysis On Willow Trees Don’t Weep Novel - Hidayah, S.S, M.A, Arini; Tri Widarwati, Nunun; Purwo Kusumo, Aji (Universitas Veteran Bangun Nusantara, 2025)
This research explains about critical discourse analysis of the novel Willow Trees Don’t Weep. It aims to understand the textual features, the discursive features, and the social features used in the novel Willow Trees Don’t Weep.The researcher used the approach of descriptive qualitative research method. The sources used in this research are: (1) documents, namely the novel Willow Trees Don’t Weep novel by Fadia Faqir and various writings or articles that support the research; and (2) informants, namely researchers who can collect data by interviewing a number of literary observers, educators/education experts. To analyze the data the writer use critical discourse analysis according to Fairclough’s theory. Conclusions are drawn based on all the things contained in data presentation. After the data are selected, classified and analyzed, the data are interpreted in critical discourse analysis which then draws a conclusion. The results of this study found 10 data in textual features, 20 data in discursive features, and 10 data in social. Textual Features, it displays forms of representation, relations, and identity. Sub-clause representations are shown in vocabulary and grammar. In this study, grammatical representations are shown more in the form of processes because they consist of actions, events, states, and mental processes. In discursive features, the context of Najwa's life and the discrimination she experienced also influenced the process. Next, the researcher analyzes how the relationship and similarities between the context presented in the discourse of the novel Willow Trees Don't Weep and the context with Najwa's real life. In Social Features, it shows that Najwa tries to change herself (physical appearance and habits) and adapts to the new culture that she meets, and she also tries to articulate her identity that influences her to strengthen her past identity or reaffirm to the new identity.